Promosi Kesehatan Oleh Kader Dan Petugas Kesehatan Tentang Pencegahan Penyakit Demam Berdarah Dengue Di Kecamatan Umbulharjo, Kota Yogyakarta - Citraningsih Yuniarti, Soesanto Tjokrosonto dan Ira Paramastri (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Discussion method of health promotion facilitated by health officer or cadre using folder is needed. The success of health promotion is depended on the skill of the facilitator to modify the behavior of other individuals. The problem is whether or not there is a difference of the skill between health officer and cadre in increasing people s knowledge about DHF prevention. The research aims to know the difference in people s knowledge of DHF prevention given by the officer and cadre.Methods: This was randomized pretest-posttest control group designs. The subject were 30 mothers who given the promotion of DHF prevention by health workers and 30 mothers were given by cadre. The technique of sampling was purposive sampling. The data were analyzed using t-test.Result: The result showed that both facilitators, health workers and cadre, improved the mothers knowledge about DHF preventation.Conclusion: Both health workers or cadre can improve mothers knowledge about DHF prevention and there was no significant difference of promotion between health workers and cadre.Keywords: health promotion, health facilitator, DHF